Silver Nanowire Networks as Transparent Conducting Films for Liquid Crystal Displays. (1st January 2015) - Park, Hong-Gyu; Heo, Gi-Seok; Park, Sang-Geon; Jeong, Hae-Chang; Lee, Ju Hwan; Seo, Dae-Shik
Abstract : In the present work, silver nanowire networks were investigated as transparent electrodes for liquid crystal display (LCD) applications, substituting indium tin oxide (ITO). Liquid crystal (LC) alignment characteristics in an LC cell using AgNW networks were similar to those of a counterpart based on ITO electrodes; however, the electro-optical (EO) characteristics were enhanced by the electric field enhancement effect of the AgNWs. Therefore, the competitive performance of the LC cell based on AgNW networks could allow new approaches to replace conventional ITO films in display technology.